Visuospatial Function in Early Alzheimer’s Disease—The Use of the Visual Object and Space Perception (VOSP) Battery - Quental, Natália Bezerra Mota; Brucki, Sonia Maria Dozzi; Bueno, Orlando Francisco Amodeo (PLOS ONE, 2013)
Alzheimer’s disease (AD) is the most frequent cause of dementia. The clinical symptoms of AD begin with impairment of memory and executive function followed by the gradual involvement of other functions, such as language, semantic knowledge, abstract thinking, attention, and visuospatial abilities. Visuospatial function involves the identification of a stimulus and its location and can be impaired at the beginning of AD. The Visual Object and Space Perception (VOSP) battery evaluates visuospatial function, while minimizing the interference of other cognitive functions. Objectives To evaluate visuospatial function in early AD patients using the VOSP and determine cutoff scores to differentiate between cognitively healthy individuals and AD patients. Methods Thirty-one patients with mild AD and forty-four healthy elderly were evaluated using a neuropsychological battery and the VOSP. Results In the VOSP, the AD patients performed more poorly in all subtests examining object perception and in two subtests examining space perception (Number Location and Cube Analysis). The VOSP showed good accuracy and good correlation with tests measuring visuospatial function. Conclusion Visuospatial function is impaired in the early stages of AD. The VOSP battery is a sensitive battery test for visuospatial deficits with minimal interference by other cognitive functions.